Martech: um estudo sobre sua aplicação no micro e pequeno varejo - Prisco, Mayara Rodrigues Laurino (2022)
Micro and small retailers suffer daily from competition, high costs and shrinking margins. With the evolution of technology, Technological Marketing, or Martech, appears as a strategy capable of generating the necessary information for this micro and small retailer to follow the competition and get to know its consumer more and more. In this context, the following question appears: How is Martech used in micro and small retailers? Thus, the general objective of this research was to identify opportunities for these entrepreneurs in the retail sector with the use of Martech to boost their business. To make the study viable, it was divided into two stages, the first being a bibliometric study in the Web of Science database, then during the data collection process, the qualitative method was chosen and in-depth interviews were applied to eight people responsible for micro and small retails. The snowball method was chosen for selection and delimitation of respondents until the saturation of information. The data analysis process took place through coding conducted with the help of the ATLAS.ti software version 07. From this process, 35 codes were categorized among the Martech tools: e-commerce, database, artificial intelligence and media. The content analysis was conducted from the categories and the results revealed that among the tools websites, sales applications, CRM, Web Analytics and research data are used by retailers, but social networks have gained prominence. In this way, it became possible to identify the use of Martech for the purpose of efficient communication, dissemination and online sales, making it possible to reach the correct audience, with lower costs and more effectively